Matters relating to the global goal on adaptation: Draft conclusions proposed by the chairs - United Nations Framework Convention on Climate Change (UNFCCC); Subsidiary Body for Implementation (SBI) (2025)
This document represents the conclusions of UNFCCC SBSTA and SBI chairs following negotiations at SB62. Notably, through the conclusions, parties provided additional criteria to guide the refinement of indicators for the Global Goal on Adaptation.